Microfluidic reactors for the size-controlled synthesis of ZIF-8 crystals in aqueous phase. (15th May 2017) - Kolmykov, Oleksii; Commenge, Jean-Marc; Alem, Halima; Girot, Emilien; Mozet, Kevin; Medjahdi, Ghouti; Schneider, Raphaël
Abstract: Zeolitic imidazolate framework (ZIF-8) crystals can be produced effectively via continuous processes using either a single water phase or a biphasic water/alkane flow in a three-dimensional microchannel. ZIF-8 particles were characterized by SEM, TEM, XRD, BET and Raman spectroscopy. The microfluidic technology developed allows the fast synthesis (10 min) of ZIF-8 crystals over a wide size range (from ca. 300 to 900 nm) simply by varying the experimental parameters (flow rates, temperature, …), while maintaining the high specific surface of this material (ca. 1700 m 2 ·g − 1 ) and the sodalite crystalline structure. The microfluidic processes developed operate in water between 25 and 100 °C and at atmospheric pressure and are therefore valuable alternatives for the environmentally friendly preparation of ZIF-8 particles. Graphical abstract: Highlights: The microfluidic technology allows the production of high quality ZIF-8 crystals. A single water phase or a biphasic flow can be used. ZIF-8 particles with sizes ranging from 300 to 900 nm can be prepared in 10 min. ZIF-8 particles exhibit a high specific surface (ca. 1700 m 2 ·g − 1 ).